Real-time loop-mediated isothermal amplification assay for rapid detection of Rift Valley fever virus - Le Roux, C.A. (Chantel Anne) (2013)
Rift Valley fever (RVF) belongs to the group of viral haemorrhagic fevers (VHFs), most of which are zoonotic diseases causing outbreaks in animals and humans all over Africa. In the absence of haemorrhagic or specific organ manifestations, these diseases are clinically difficult to diagnose. Rapid laboratory confirmation of cases is therefore essential for timely execution of supportive treatment, appropriate case management, infection control, and tracing of contacts. Rift Valley fever virus (RVFV), a mosquito-borne pathogen, is responsible for high mortality rates and abortion in domestic ruminants, resulting in significant socio-economic losses. Furthermore, the virus is potentially infectious by aerosol, can replicate in a wide range of mosquito species and poses a bioweapon threat. The recent spread of the virus outside of the African continent, demonstrates its ability to move northwards to RVF free regions, e.g. to Europe and Northern America. Such fears fuel the international demand for reliable and validated diagnostic tools for rapid diagnosis of RVF. The aim of this study was to develop a rapid and accurate molecular tool for the detection of RVFV. A real-time loop-mediated isothermal amplification assay (LAMP) targeting the L segment of RVFV, was developed and evaluated. The assay proved to be highly specific and able to detect RVFV strains representing the genetic spectrum of the virus. Furthermore, the assay did not amplify the RNA of other genetically and antigenically related phleboviruses. The sensitivity of the assay was compared to that of a previously published TaqMan RTD-PCR protocol and found to be equal. Similarly, the assay demonstrated very high diagnostic sensitivity and specificity in various clinical human and animal specimens, collected during natural outbreaks of the disease in Africa. The detection of specific viral genome targets in positive clinical specimens was achieved in less than 30 minutes. As a highly accurate, rapid and very simple nucleic acid detection format, the RT-LAMP assay has the potential to be used in less well equipped laboratories in Africa. The assay format can be adapted to a portable device that can be utilized during RVF outbreaks in remote areas, and can be a valuable tool for differential diagnosis of VHFs. === Dissertation (MSc)--University of Pretoria, 2010. === Microbiology and Plant Pathology === unrestricted